PERCEPTION OF HORTICULTURISTS ON NEMATODE PESTS OF ORNAMENTAL PLANTS AND THE LIKELIHOOD OF SOIL AS PRIMARY SOURCE OF INFECTION - Tanimola, Adebowale Adegboyega; Nwokogba, S. O.; Oladele, A. T.; Oladele, A. T. (FUDMA JOURNAL OF SCIENCES, 2020)
Nematode pests contribute significantly to poor growth and losses in ornamental plants. However, majority of ornamental garden operators have little or no knowledge of these nematode pests. This study assesses the perception of horticulturists on plant-parasitic nematodes (PPNs) of ornamental plants in Port Harcourt metropolis. A total of 23 ornamental gardens were randomly chosen and visited. Structured questionnaire was randomly administered directly to all operators in collection of data and options were given in code to rank the results. A total of fifty-three soil samples were collected from all the gardens visited. Nematode pests were extracted from the samples using standard procedures. Data were processed using descriptive statistics, diversity indices, relative importance value (RIV) and analysis of variance. The results showed that 95.7% of the horticulturists were male, 78.2% were youth, while 100.0% of the ornamental garden owners had no knowledge of nematode pests attacking ornamental plants. Four nematode pest genera, Meloidogyne, Pratylenchus, Tylenchulus and Helicotylenchus were found in the soil being used for propagation by these horticulturists. However, Meloidogyne species with the RIV of 40.45% were the most important genus and the most frequently encountered nematode pest (relative frequency of occurrence of 19.35%). Hilltop horticultural garden had the highest mean population of PPNs, but not significantly more than PPNs in other gardens. The study revealed that nematode pests are one of the major bio constraints to ornamental plants and that soil if not treated could be a primary source of nematode infection.